PERAN UNITED NATIONS OFFICE ON DRUGS AND CRIME (UNODC) DALAM PENANGGULANGAN HIV/AIDS DI INDONESIA - Dyanni Syifa Amira; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Indonesia has a very large area. This leaves Indonesia vulnerable to traditional security threats, namely threats involving the military sector and nontraditional threats, namely threats to human security such as infectious diseases. The HIV/AIDS epidemic is a problem that can threaten human security and occurs in every country in the world. It is not only countries that are actors in tackling the HIV/AIDS epidemic. International Organizations have an important role to play in helping countries in the fight against HIV /AIDS. The United Nations Office on Drugs and Crime (UNODC) is an international organization that has a mandate to fight HIV / AIDS and has a role in the fight against HIV / AIDS in Indonesia. This research uses a Pluralisne perspective with a level of group analysis / theory used in this research is the international organizational theory of Clive Archer and the concept of Human Security from Barry Buzan. Qualitative methods in this study use primary data sourced from interview results and secondary data sourced from official websites, books, journals, articles, and websites. This research shows that the presence of UNODC in Indonesia has an important role in the fight against HIV / AIDS. The Indonesian government also assesses that UNODC is a partner that has a great influence on the management of various problems in Indonesia. The role of the UNODC organization in tackling HIV / AIDS in Indonesia is as an instrument. UNODC is a tool for Indonesia in achieving its goals and interests in tackling HIV/AIDS by formulating the Indonesia Country Programme 2017-2020. Keywords: United Nations Office on Drugs and Crime, HIV/AIDS Epidemic, International Organization Theory, Pluralism, The Concept of Human Security,